A simulation model for choosing strategies for the interaction of business and government in implementing public-private partnership programs - Chuprina, Yu. (Ways to Improve Construction Efficiency, 2018)
Directions for improving the tools of state regulation of construction by developing targeted programs of public-private partnership are proposed. The formation of the program-targeted methods of regulation in the historical aspect, the legislative and regulatory framework, the dynamics of the development of this process are considered. Destructive factors that interfere with the effective implementation of state regulation of construction were identified, including the lack of preventive measures to prevent negative development, inconsistency of goals, lack of choice of priorities, proper control, and methods for evaluating the effectiveness of programs. It was revealed that the components of the mechanism of state regulation of construction that require improvement are the system of assessing the impact of public policy instruments (budget, tax, tariff, customs, regulatory) and the planning of capital and current costs. It is proposed to use program-targeted methods of regulation more widely in the formation of mechanisms of state regulation by construction; at present, it is a pivotal element of state regulation.